Development of Carbon Fiber Composite Material Blades for Vertical Axis Wind Turbines as an Alternative Energy Source for Street Lights for a Speed Range of 2-8 m/s - Soetanto, Maria Fransisca; Hidayat, Syarif; Iryani, Lenny; Subardjah, Adri Maldi; Hartono, Budi; Rosalia, Citra Asti (International Journal of Integrated Engineering, 2025)
Global warming causes weather anomalies in urban areas in Indonesia, causing wind speeds of 6-7 m/s, far above the normal average speed of 2-4 m/s, causing damage to the vertical axis wind turbine (VAWT) blades made from duralumin material, which is used to drive street lights in rural Bandung, West Java- Indonesia. So, it is necessary to use stronger blade material to anticipate the forces generated due to wind speed anomalies, besides that it must also be able to function at low wind speeds: and the composite material used in this research is carbon fiber material. This paper discusses the development of vertical axis wind turbine blades with blades made from carbon fiber composite materials and compares their durability duralumin blades. The research began with making carbon fiber composite material specimens to then be tested for impact strength and bending strength respectively according to ASTM D790-03 and ASTM D6110-08 standards. The VAWT models for both blade material variants were made at a scale of 1:3 and the durability performance was tested in the wind tunnel. The result is that the VAWT with carbon fiber blade material is able to withstand vibrations up to 50% compared to the duralumin blade VAWT at a wind speed of 8 m/s. The tensile strength of carbon fiber is 8.86% greater than the tensile strength of duralumin, and the impact strength of carbon fiber is 13.36% greater than duralumin, so that the use of carbon fiber composite material as a VAWT blade can be used for wind speed anomalies up to 8 m/s.